Having a creative day: Understanding entrepreneurs' daily idea generation through a recovery lens - Weinberger, Eva; Wach, Dominika; Stephan, Ute; Wegge, Jürgen (Journal of Business Venturing, 2018)
Prior research has shown that trait creativity is important for becoming an entrepreneur and successful in business. We explore a new perspective by investigating how recovery from work stress influences entrepreneurs' daily idea generation, a key aspect of creativity. Physiological and mental recovery enables the cognitive processes of creative problem-solving. Moreover, differences in mental recovery processes help to explain age-related changes in entrepreneurs' creativity. Multilevel analyses based on 415 daily data from 62 entrepreneurs support our predictions. Our study introduces a new “state” perspective to understanding entrepreneurs' creativity, and highlights the critical role of recovery processes for idea generation.